ANALISIS STRUKTUR ORGANISASI DAN PEMBAGIAN KERJA DALAM PERSPEKTIF PRINSIP SYARIAH PADA PERUSAHAAN - Duwi Lestari; Erwina Mutiara Sari; Novian Naufa Sari; Dafi Naufalingga; Cindi Melinda Sari (JSE: Jurnal Sharia Economica, 2026)
Organizational structure and division of labor are essential elements in management systems that contribute to organizational effectiveness and efficiency. However, in practice, several problems still occur, such as unclear responsibilities, unequal workload distribution, and the lack of ethical values in organizational management. In the Islamic perspective, organizational management is not merely oriented toward managerial efficiency but must also be based on Sharia principles such as trust (amanah), justice, consultation (shura), and cooperation. This study aims to analyze organizational structure and division of labor from the perspective of Sharia principles. This research employs a qualitative approach using a library research method. Data were collected from various literature sources, including books, scholarly articles, and relevant academic documents. The data were analyzed using a descriptive qualitative method by examining the concepts of organizational structure and division of labor in modern management theory and integrating them with Islamic management principles. The results indicate that organizational structure and division of labor in the Sharia perspective function not only as an administrative system for managing organizations but also as instruments to realize values of justice, responsibility, and cooperation in organizational activities. The integration of modern management concepts with Sharia principles can create a more effective, ethical, and sustainable organizational management system.